Rate of change in body mass index at different ages during childhood and adult obesity risk. Issue 7 (31st January 2019) - Zhang, Tao; Whelton, Paul K.; Xi, Bo; Krousel‐Wood, Marie; Bazzano, Lydia; He, Jiang; Chen, Wei; Li, Shengxu
Summary: Background: Childhood body mass index (BMI) predicts adult obesity. How growth trajectories during childhood relate to adult obesity risk is not well defined. Objective: We aimed to characterize BMI growth trajectories from childhood to midlife and to examine the associations between BMI growth rates at childhood age points and adult obesity risk. Methods: The longitudinal study included 2732 participants with repeated BMI measurements from childhood (4‐19 y) to adulthood (20‐51 y). A random‐effects model was used to construct BMI growth curves by race and sex. Model‐estimated levels and linear growth rates of BMI were linked to adult obesity in separate multivariable logistic regression models at individual childhood age points. Results: BMI followed cubic growth curves. Childhood BMI linear slope estimates were higher in adults with obesity than in adults without obesity ( P  < 0.001). The association between childhood BMI growth rate and adult obesity was significantly higher in puberty and postpuberty (12‐19 y) than in early childhood (4‐11 y) with a peak at age 14 (odds ratio = 3.1 and 95% confidence interval, 2.7‐3.5). Conclusions: Rates of change in BMI at different childhood ages are differentially associated with adult obesity. Puberty and postpuberty are crucial periods for the development of obesity in later life.